Ionization satellites of the ArHe dimer - Miteva, Tsveta; Klaiman, Shachar; Gromov, Evgeniy; Gokhberg, Kirill (The journal of chemical physics, 2014)
Ionization satellites are key ingredients in the control of post ionization processes such as molecular dissociation and interatomic Coulombic decay. Here, using the high-level ab initio method of multi-reference configuration interaction up to triple excitations, we study the potential energy curves (PECs) of the ionization satellites of the ArHe dimer. With this model system, we demonstrate that the simple model used in alkaline earth metal and rare gas complexes to describe the satellites as a Rydberg electron moving on top of a dicationic core does not fully hold for the rare gas clusters. The more complex valence structure in the rare gas atom leads to the mixing of different electronic configurations of the dimer. This prevents one from assigning a single dicationic parent state to some of the ionization satellites. We further analyze the structure of the different PECs, demonstrating how the density of the Rydberg electron is reflected in the structure of the PEC wherever the simple model is applicable.